Collagen Cross-Linking: Current Status and Future Directions - Marine Hovakimyan; Rudolf F. Guthoff; Oliver Stachs (Journal of Ophthalmology)
Collagen cross-linking (CXL) using UVA light and riboflavin (vitamin B2) was introduced as a clinical application to stabilize the cornea by inducing cross-links within and between collagen fibers. CXL has been investigated extensively and has been shown clinically to arrest the progression of keratoconic or post-LASIK ectasia. With its minimal cost, simplicity, and proven positive clinical outcome, CXL can be regarded as a useful approach to reduce the number of penetrating keratoplasties performed. Small case series have also indicated that CXL is beneficial in corneal edema by reducing stromal swelling behavior and in keratitis by inhibiting pathogen growth. Despite these encouraging results, CXL remains a relatively new method that is potentially associated with complications. Aspects such as side effects and recurrence rates have still to be elucidated. In light of the growing interest in CXL, our paper summarizes present knowledge about this promising approach. We have intentionally endeavored to include the more relevant studies from the recent literature to provide an overview of the current status of CXL.